New Pickering emulsions stabilized with chitosan/collagen peptides nanoparticles: Synthesis, characterization and tracking of the nanoparticles after skin application - Sharkawy, Asma (2018)
Pickering emulsions based on biopolymeric particles are gaining increasing research recognition in numerous applications due to their biocompatibility and eco-friendliness. In this work, chitosan/collagen peptides nanoparticles were applied to stabilize Pickering emulsions for potential cosmetic applications. The nanoparticles had a contact angle of 78.02° ± 2.04°, reflecting their hydrophilic nature. Their average size and zeta potential were 32.27 nm and +59.7 mV, respectively. Confocal laser scanning microscopy (CLSM) showed that the nanoparticles become well-adsorbed at the oil-water interface. The emulsions displayed shear-thinning viscosity and gel-like texture. Their average droplet size ranged between 7.63 μm and 15.72 μm. CLSM skin tracking of the nanoparticles, after ex vivo skin application of the Pickering emulsions, revealed the ability of the emulsion droplets to penetrate the stratum corneum and deposit in deeper skin layers. The penetration degree depends on the concentration of the nanoparticles in the emulsion and on the contact time with the skin. These results provide new insights into the fate of the nanoparticles used to stabilize Pickering emulsions following their skin application.